STUDY OF PHOSPHATE SOLUBILIZING FUNGI IN PEAT SOIL IN SEVERAL TYPES OF LAND USE OF SIANTAN HILIR VILLAGE PONTIANAK CITY - Ariska, Nunung; Umran, Ismahan; Nusantara, Rossie Wiedya (Fakultas Pertanian Universitas Tanjungpura, 2019)
The use of peat land for agriculture is growing rapidly. However, in this utilization various problems were encountered, one of which was the strength of phosphate nutrients. One alternative to overcome the low availability of phosphate is to use a phosphate solvent fungus. This study aims to determine the population and type of phosphate solubilizing fungus and the population differences in several peatland uses (oil palm, pineapple, mustard, aloe, papaya and secondary forest) and to know the ability of fungi to dissolve phosphate nutrients. The methods used in this study are preparation, selection and observation of the location of the study, determination of sampling points, soil sampling (microbiology specific soil samples, sample samples and disturbed soil samples), preparation and sterilization of equipment and media in the laboratory, calculation and isolation fungus phosphate solubilizing colonies. The results showed that the highest population of phosphate solubilizing fungus (CPF) was found on pineapple land which was as much as 2.99 x 104 CFU / ml, and the lowest on aloe vera land was 2.11 x 104 CFU / ml. The analysis of the diversity of CPF population numbers on six land uses showed that the number of CPF populations had no significant effect. The types of fungi found were 13 types of solubilizing fungi. The land use which has the most phosphate solvent fungus types is oil palm and pineapple land. The ability of the fungus to dissolve phosphate can be seen from how large the clear zone is formed. Land use which has the largest area of clear zone is found in oil palm land which is equal to 242.31 mm2 and the smallest on pineapple land which is equal to 118.74 mm2. The test results of the analysis of the wide diversity of clear zones on aloe vera, papaya, mustard, oil palm, pineapple and secondary forest showed that the area of clear zones had no significant effect on land use. The land use system influences the diversity of phosphate solubilizing microorganisms and the ability to dissolve phosphate but the land use system does not affect the population of phosphate solubilizing fungi. Keywords: Phosphate Solubilizing Fungi, Phosphate, Peat Soil, Phosphate Solubilizing Microorganism, Clear Zone